Semiprime SF-rings whose essential left ideals are two-sided - Zhang Jule; Du Xhianneng (International Journal of Mathematics and Mathematical Sciences)
It is proved that if R is a semiprime ELT-ring and every simple right R-module is flat then R is regular. Is R regular if R is a semiprime ELT-ring and every simple right R-module is flat? In this note, we give a positive answer to the question.